Building customer loyalty at Balung Regional Hospital with a Service Encounter and Satisfaction Strategy - Robustin, Tri Palupi; Putri, Nur Latifa Isnaini; Hakim, Ikhwanul (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
A service encounter, sometimes referred to as a service meeting, is an essential part of the process by which service providers deliver services to their clients effectively and efficiently. This process plays a key role in shaping how customers perceive a company and fostering their long-term loyalty through positive interactions. This study seeks to explore how service encounters, customer satisfaction, and their combination influence customer loyalty at Balung Regional Hospital. The research conducted at Balung Regional Hospital involves quantitative analysis focusing on all service users comprehensively. The sampling technique employed is non-probabilistic, specifically purposive sampling, involving a sample size of 60 respondents carefully selected. This research uses multiple linear regression analysis to evaluate the data accurately. The results of the study show that: (1) Service encounter significantly affects customer loyalty in Balung Regional Hospital; (2) Satisfaction positively affects customer loyalty of Balung Regional Hospital; (3) Service encounter and satisfaction have a simultaneous effect on customer loyalty of Balung Regional Hospital, highlighting their interdependence.